Infectious disease and bioterrrorism: disaster to public health and security in Malaysia - Nor Anita Abdullah; Rohani Abdul Rahim (Penerbit Universiti Kebangsaan Malaysia, 2016)
World Health Organization (WHO) outlined that the emergence of infectious diseases represent a global threat that will require a coordinated and global response. The threat is considered as global because the nature of the diseases itself to emerge anywhere and everywhere in the planet and widespread to other regions. The recent emergence of infectious disease known as Zika virus which the WHO says is “spreading explosively” across the Americas. Malaysia had issued a health alert to the public in alarming its citizen to be in the state of precaution. The rise of security in the event of new and re-emerging infectious diseases on the national security agenda has provoked a number of debates among Malaysian stakeholders. There is an issue of linkage between public health and security as disaster issue under the national agenda. This article attempt to analyze the emergence of newly and existing infectious diseases having a potential of causing bioterrorism in order to identify the linkage between the public health issues with the security under the national agenda as disaster. Thus, there must be a turning point in the consideration of public health issue in linking it with the security issue especially in the event of any possibility of bioterrorism to ensure a world safe and secure from any possibility of bioterrorism in the form of emerging infectious diseases (EID). Thus, this article also plans to propose a public health and security policies on managing and handling the possibility of bioterrorism event as disaster in Malaysia.